If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -4 = 11 Reorder the terms: -4 + 2y = 11 Solving -4 + 2y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2y = 11 + 4 Combine like terms: -4 + 4 = 0 0 + 2y = 11 + 4 2y = 11 + 4 Combine like terms: 11 + 4 = 15 2y = 15 Divide each side by '2'. y = 7.5 Simplifying y = 7.5
| 6x-5=2x+9 | | 288-4x=41x+23 | | 2(4x-3)=14 | | 2x+29=9x-34 | | -5g-(11-2g)=-(g+8)+5 | | 5y+3=3y+10 | | 2x+5=23-x | | 5-8x=32-15x | | 2x-5=11x-34 | | w-3=9 | | 5(a+1)=42.5 | | 11x-5=9x+1 | | x+2x=12 | | 9.4=4c-9 | | 2x+x=21 | | y-3=11 | | 4x^2-3x+7=5x+4 | | 102-4x=23x+24 | | 6x^2-47x-63=0 | | 15x-186=6x-6 | | 8e-6=44.4 | | 5(2y+3)=20 | | 5(t-3)=8 | | 5(t-8)=8 | | 2p=7.6 | | 4y+3=2y+9 | | 5x=50 | | 6x+46=10x+10 | | 7-9x=71-23x | | 5x+5=50 | | 17-4x=10+3x | | 9r+10r+r= |